Effects of distance from semi-natural habitat on fall armyworm (Spodoptera frugiperda, J. E. Smith) and its potential natural enemies in Ghana - Jordon, MW; Hackett, TD; Aboagye-Antwi, F; Eziah, VY; Lewis, OT (Cambridge University Press, 2021)
Insect crop pests are a major threat to food security in sub-Saharan Africa. Configuration of semi-natural habitat within agricultural landscapes has the potential to enhance biological pest control, helping to maintain yields whilst minimising the negative effects of pesticide use. Fall armyworm (Spodoptera frugiperda, J. E. Smith) is an increasingly important pest of maize in sub-Saharan Africa, with reports of yield loss between 12 and 45%. We investigated the patterns of fall armyworm leaf damage in maize crops in Ghana, and used pitfall traps and dummy caterpillars to assess the spatial distribution of potential fall armyworm predators. Crop damage from fall armyworm at our study sites increased significantly with distance from the field edge, by up to 4% per m. We found evidence that Araneae activity, richness and diversity correspondingly decreased with distance from semi-natural habitat, although Hymenoptera richness and diversity increased. Our preliminary findings suggest that modifying field configuration to increase the proximity of maize to semi-natural habitat may reduce fall armyworm damage and increase natural enemy activity within crops. Further research is required to determine the level of fall armyworm suppression achievable through natural enemies, and how effectively this could safeguard yields.